Ultrafine particles: Levels in ambient air during outdoor sport activities. (March 2020) - Slezakova, Klara; Pereira, Maria Carmo; Morais, Simone
Abstract: Conducting aerobic activity on regular basis is recognised as one of the steps to maintain healthier lifestyle. The positive outcomes though can be outweighed if conducted in polluted atmosphere. Furthermore, the specific inhalation during exercising, which results in bypass of nasal filtration systems and deeper penetration into the respiratory system, might result in higher risks especially to pollutants such as ultrafine particles (UFP), which aerodynamic particle diameter are <100 nm. Thus, this work aims to evaluate UFP levels at sites used for conducting physical sport activities outdoors and to estimate the respective inhalation doses considering various scenarios and different physical activities. Monitoring of UFP was conducted during three weeks (May–June 2015) at four different sites (S1–S4) regularly used to conduct physical exercising. The results showed that UFP highly varied (medians 5.1–20.0 × 10 3 # cm −3 ) across the four sites, with the highest UFP obtained when exercising next to trafficked streets whereas S3 and S4 (a garden and city park) exhibited 2–4 times lower UFP. In view of the obtained UFP concentrations, the estimated inhalation doses ranged 1.73 × 10 8 –3.81 × 10 8 # kg −1 when conducting moderately intense sport activities and 1.93 × 10 8 –5.95 × 10 8 # kg −1 for highly intense ones. Highly intense activities ( i.e. running) led to twice higher UFP exposure; children and youths (5–17 yrs old) experienced 203–267% higher doses. Considering the age– and gender– differences, estimated UFP doses of males were 1.1–2.8 times higher than of females. Finally, UFP inhalation doses estimated for walking (commuting to work and/or schools) were 1.6–7.5 times lower than when conducting sport activities. Thus to protect public health and to promote healthy and physically active lifestyle, strategies to minimize the negative impacts of air pollution should be developed and implemented. Graphical abstract: Image 1 Highlights: Ultrafine particles levels (UFP) while exercising outdoors were monitored. The obtained UFP ranged between 5.1 and 20.0 × 10 3 # cm −3 across four sites. At trafficked streets UFP levels were 2–4 times higher than at a park and a garden. UFP levels were associated with meteorological parameters (T, RH, wind speed). Estimated inhalation doses were ∼ twice higher for highly intense sport activities. Abstract : This work fills a gap providing information on levels of ultrafine particles during conducting different outdoor physical activities.